Ordovician conodont biogeography - Econsidered - Zhen, Yong Yi; Percival, Ian G. (Lethaia, 2003)
Review of the traditional separation of global Ordovician conodont distribution into the North American Midcontinent Province (NAMP) and North Atlantic Province (NAP) reveals a confusing variety of concepts and definitions that hinder biogeographic analysis. Use of this twofold scheme and its subsequent variants should be discontinued in favour of the more detailed divisions proposed here. Major biogeographical entities of the Shallow-Sea and Open-Sea Realms, separated by the shelf-slope break, are both further subdivisible into Tropical, Temperate and Cold Domains. In the Cold domains, faunal differences between the two Realms and their subdivisions are not easily discernible, since biofacies zones and different habitats were highly condensed. Faunal differences are amplified in the tropical regions, where the North American Midcontinent Province and North Atlantic Province were originally defined. Recognition of endemic taxa is essential for finer classification within domains of the Shallow-Sea Realm (SSR). Our preliminary analysis of Early Ordovician conodont distribution identifies the Laurentian Province (in the Tropical Domain), Australian (Tropical Domain), North China (Tropical Domain), South China (Temperate Domain), Argentine Precordillera (Temperate Domain) and Balto-Scandian Province (in the Cold Domain). The Open-Sea Realm (OSR) is dominated by cosmopolitan and widespread taxa, and formal subdivision at provincial level is yet to be achieved. The North Atlantic Province encompasses both the Open-Sea Realm and the Temperate and Cold Domains of the Shallow-Sea Realm. The North American Midcontinent Province sensu stricto is more or less equivalent to the Laurentian Province, representing shallow-water regions fringing Laurentia; in a broader sense the North American Midcontinent Province includes all provinces of the Tropical Domain within the Shallow-Sea Realm.